A new cotton functionalized with iron(III) trimer-like metal framework as an effective strategy for the adsorption of triarylmethane dye: An insight into the dye adsorption processes - Conde-González, J E; Lorenzo-Luis, P; Salvadó, V; Havel, J; Peña-Méndez, E M (Heliyon, 2021)
A new Cotton@Fe-BTC composite formed by Fe-BTC (BTC-H3: trimesic acid) metal framework (Fe-BTC MOF loading as high 38 wt %) supported by cellulose fiber is synthesized in aqueous media using a simple and green preparation method, described for the first time in this manuscript. This new strategy relies on the synergetic effect of the pure cellulose and MOFs frameworks resulting in hybrid nanofibers of MOFs@cellulose composite. A complete characterization of the composite material reveals its structural similarity to MIL-100(Fe), a Fe-BTC material. The Cotton@Fe-BTC composite potential use as an eco-friendly and low-cost adsorbent was evaluated for its adsorptive performance for the removal of dye belonging to the triarylmethane dye family (Malachite Green (MQ), Brilliant Green (BG), Pararosaniline (PR), Basic Fuchsine (BF), Crystal Violet (CV), Methyl Green (Met-G), Victoria Blue B (VB), Acid Fuchsin (AF) and Aniline Blue (AB)) in aqueous solution. The fast kinetics and high dye removal efficiencies (>90%) obtained in aqueous solutions. The structure of Cotton@Fe-BTC network, contributed to the remarkable adsorption properties towards a variety of triphenylmethanedye. The interparticle studies showed two main steps in the dye adsorption processes, with the exception of AF and BG. The equilibrium adsorption capacities qe (mg/g) follow the order: AF (3.64)<Met-G (3.70)<AB (4.87)<PR (5.52)<BF (5.76)< Met-G (7.22)<CV (9.63)<BG (16.34). However, going insight the adsorption mechanisms, it was remarkable the finding that the reaction paths taking into account the influence of water molecules on the anionic dye adsorption, through the so-called solvation/desolvation penalty processes, may not be ignored. The easy preparation and manipulation of Cotton@Fe-BTC network as well as its stability and excellent performance for the adsorption makes this material a good candidate for a broad range of applications.
Keywords: Solvation/desolvation penalty processes; Natural cotton; Water; Adsorption; Fe-BTC; Triphenylmetane dye